Apigenin as Tumor Suppressor in Cancers: Biotherapeutic Activity, Nanodelivery, and Mechanisms With Emphasis on Pancreatic Cancer - Ashrafizadeh, Milad; Bakhoda, Mohammad Reza; Bahmanpour, Zahra; Ilkhani, Khandan; Zarrabi, Ali; Makvandi, Pooyan; Khan, Haroon; Mazaheri, Samaneh; Darvish, Maryam; Mirzaei, Hamed (Frontiers in Chemistry, 2020)
Pancreatic cancer is the most lethal malignancy of the gastrointestinal tract. Because of its propensity for early local and distant spread, affected patients possess extremely poor prognosis. Currently applied treatments are not effective enough to eradicate all cancer cells, and minimize their migration. Besides, these treatments are associated with adverse effects on normal cells and organs. These therapies are not able to increase the overall survival rate of patients; hence, finding novel adjuvants or alternatives is so essential. Up to now, medicinal herbs were utilized for therapeutic goals. Herbal-based medicine, as traditional biotherapeutics, was employed for cancer treatment. Of them, apigenin, as a bioactive flavonoid that possesses numerous biological properties (e.g., anti-inflammatory and anti-oxidant effects), has shown substantial anticancer activity. It seems that apigenin is capable of suppressing proliferation of cancer cells via induction of cell cycle arrest and apoptosis. Besides, apigenin inhibits metastasis via down-regulation of matrix metalloproteinases and Akt signaling pathway. In pancreatic cancer cells, apigenin sensitizes into chemotherapy, and affects molecular pathways such as hypoxia inducible factor (HIF), vascular endothelial growth factor (VEGF), glucose transporter-1 (GLUT-1), etc. Herein, the biotherapeutic activity of apigenin and its mechanisms toward cancer cells are presented in the current review to shed some light on anti-tumor activity of apigenin in different cancers, with an emphasis on pancreatic cancer.